2005
DOI: 10.1002/pmic.200401153
|View full text |Cite
|
Sign up to set email alerts
|

Probing heat-stable water-soluble proteins from barley to malt and beer

Abstract: Proteins determine the quality of barley in malting and brewing end-uses. In this regard, water-soluble barley proteins play a major role in the formation, stability, and texture of head foams. Our objective was to survey the barley seed proteins that could be involved in the foaming properties of beer. Therefore, two-dimensional (2-D) electrophoresis and mass spectrometry were combined to highlight the barley proteins that could resist the heating treatments occurring during malting and brewing processes. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
165
2
6

Year Published

2007
2007
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(180 citation statements)
references
References 32 publications
7
165
2
6
Order By: Relevance
“…It has been shown that the molds and bacteria in barley increase during malting, reaching a peak during the germination stage (Flannigan 2003), consistent with the observation that defense and stress response genes increased from steeping to day 4. Analysis of the proteome of malt and beer also showed the predominance of proteins involved in protection against pathogens and insects (Perrocheau et al 2005). In addition, seed germination may be considered a critical time point in a plant's life cycle and it is not surprising that a large number of defense-related genes are normally upregulated as a protective measure.…”
Section: Transcript Prowles Of Germinating Barley Seedsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the molds and bacteria in barley increase during malting, reaching a peak during the germination stage (Flannigan 2003), consistent with the observation that defense and stress response genes increased from steeping to day 4. Analysis of the proteome of malt and beer also showed the predominance of proteins involved in protection against pathogens and insects (Perrocheau et al 2005). In addition, seed germination may be considered a critical time point in a plant's life cycle and it is not surprising that a large number of defense-related genes are normally upregulated as a protective measure.…”
Section: Transcript Prowles Of Germinating Barley Seedsmentioning
confidence: 99%
“…Other genes that were up-regulated from germination through kilning included those coding for peptidases, lipid transfer proteins, and proteinase inhibitors. These proteins were identiWed as thermostable components of malt and beer (Perrocheau et al 2005). Other genes that were up-regulated from germination to kilning were those for heat shock proteins, which function to protect enzymes during heat stress (Jinn et al 1995;Waters et al 1996).…”
Section: Transcript Prowles Of Germinating Barley Seedsmentioning
confidence: 99%
“…A biphasic expression, similar to the expression of the TLP genes in barley and oat seeds 308 , has been reported for serpins 282 . Recent proteomics studies have confirmed the presence of high amounts of acidic proteins identified as protein Z in barley and malt, and a third isoform, Zx, which was not previously detected 247,260 . Analysis of the peripheral granule proteome in barley endosperm revealed only presence of BSZ4 27 .…”
Section: Chymotrypsin/subtilisin Inhibitors (Ci-1 and Ci-2)mentioning
confidence: 99%
“…They probably play a role in the dough aqueous phase and the dough's ability to form an elastic interface lining the bubbles, maintaining integrity during dough proving 291 . Proteomics has enabled the identification of CMs (CMb, BDAI-1, BTI-CMe2.1, BMAI-1) in beer 260 . These could affect beer foam quality and participate in haze formation.…”
Section: Chymotrypsin/subtilisin Inhibitors (Ci-1 and Ci-2)mentioning
confidence: 99%
See 1 more Smart Citation